2022
DOI: 10.3390/plants11101373
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Plant Grafting Technique with Dielectric Barrier Discharge Cold Atmospheric Plasma and Plasma-Treated Solution

Abstract: A garden plant grafting technique enhanced by cold plasma (CAP) and plasma-treated solutions (PTS) is described for the first time. It has been shown that CAP created by a dielectric barrier discharge (DBD) and PTS makes it possible to increase the growth of Pyrus communis L. by 35–44%, and the diameter of the root collar by 10–28%. In this case, the electrical resistivity of the graft decreased by 20–48%, which indicated the formation of a more developed vascular system at the rootstock–scion interface. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…The lower the active resistance (the real part of the impedance), the better the graft union formed. As shown by previous studies on pear and cherry trees [ 31 , 55 ], lower values of the active part of the impedance correlated with a higher rate of plant biomass gain during the first 6 months of development. As can be seen from Figure 13 , this result was also reproduced for apple samples.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The lower the active resistance (the real part of the impedance), the better the graft union formed. As shown by previous studies on pear and cherry trees [ 31 , 55 ], lower values of the active part of the impedance correlated with a higher rate of plant biomass gain during the first 6 months of development. As can be seen from Figure 13 , this result was also reproduced for apple samples.…”
Section: Discussionsupporting
confidence: 62%
“…EIS is an alternative technology to existing methods that is already showing promising results in the agro-food industry [ 37 , 38 ], where it is used for a wide range of applications, such as the assessment of injury healing in fruit plants [ 31 ], grading and quality control of vegetables [ 39 , 40 , 41 ], fruit [ 42 , 43 ], meat [ 44 ], fish [ 45 , 46 ], and honey [ 47 ], as well as for pesticide detection [ 48 ] and the valorization of agro-food waste [ 49 ]. A relationship has also been established between the electrical behavior of biological tissue and changes in its properties due to freezing [ 50 ] or drying [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic background, working solution concentrations, handling, and other factors can also influence the responses of plants. For instance, in our previous research we observed an increase of survival rate of cherry and pear graftings with PAW up to 11% compared to non-treated PAW grafts [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cold plasma has already proved its effectiveness in the destruction of cancer cells in vitro [ 1 , 2 , 3 , 4 ] and in vivo [ 2 , 4 ]. In parallel with the direct effect of cold plasma on biological objects, the properties of solutions treated with such plasma and their possible impact on biological objects are currently being investigated by various authors [ 5 , 6 , 7 , 8 ]. The use of such plasma-treated solutions in oncology is of the greatest interest since, in most cases, cancer cells are not readily accessible for direct cold plasma treatment without surgical interventions.…”
Section: Introductionmentioning
confidence: 99%